1990
DOI: 10.1016/0014-5793(90)80031-d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a reversible structural transition in the metal‐depleted glycerol dehydrogenase from Bacillus stearothermophilus

Abstract: Evidence is presented to demonstrate that the Znzf -depleted, inactive form of the glycerol dehydrogenase from BaciNus stearothermophifw exists in one of two possible conformations in equilibrium, the position of which is temperature sensitive. The conformation of the metal-depleted enzyme favoured by higher temperatures (20-4O"C) is able to bind Zn2+ and regain catalytic activity, whereas that favoured at lower temperatures (0-10X') is unable to bind metal ions and is thus inactive. This equilibrium is also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In the light of these results, we suggest that PEG may prevent GlyDHs from losing their quaternary structure under alkaline conditions (Spencer et al, 1990) but does not interfere significantly with the immobilization chemistry so far.…”
Section: Optimization Of Immobilization Under Alkaline Conditionsmentioning
confidence: 83%
See 1 more Smart Citation
“…In the light of these results, we suggest that PEG may prevent GlyDHs from losing their quaternary structure under alkaline conditions (Spencer et al, 1990) but does not interfere significantly with the immobilization chemistry so far.…”
Section: Optimization Of Immobilization Under Alkaline Conditionsmentioning
confidence: 83%
“…This case is especially dramatic for GlyDH-Gs likely because it is an octameric enzyme fully that fully loses its quaternary structure at pH 9.5-10 as it has been previously reported (Ruzheinikov et al, 2001). This fact can even occur under pH 8 when one Zn 2+ -that plays a catalytic role -is previously depleted (Spencer et al, 1990). Therefore, it seems that alkaline conditions are the major cause for the GlyDH inactivation during the immobilization on Ag-G; the high pH values may drive to lose the enzyme quaternary structure, leading them to the inactivation.…”
Section: Immobilization Of Glydhsmentioning
confidence: 99%
“…As shown above, the concentration-independent refolding is completed after about 10 s. The lag phase for reassociation takes up to 5 min possibly indicating that the formation of inactive dimers precedes the formation of the active tetramer. Taking into account that wild-type Zn2+-GDH is always found as an oligomer and that apo-GDH is stable as a tetramer at pH values below 8.0 [41], it is probable that the metal ions bind to the tetramer, the stabilisation of that oligomer pulling the equilibrium between different species towards increased levels of reassociation. The same activation mechanism could be envisaged for the cofactor NADH, implying perhaps that both Zn2+ and NADH only bind to oligomers, possibly to sites that overlap two subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the subunits contain one Zn2+ ion which is required for catalytic activity although other divalent cations such as Cd", Coz+, and Mn2+can alternatively be bound by the metal-depleted enzyme (apo-GDH) to restore activity [39,401. The metal ions may also have a structural role since tetrameric, apo-GDH is both inactive and shows a tendency, particularly in Tris or triethanolamine-based buffers, to dissociate at pH values above pH 8.0 [41]. Chemical modification and protein sequencing studies have shown that the unique cysteine residue in each subunit (C208) is probably involved in metal ion ligation and that modification of this residue by methylmethanesulphonic acid (only possible in the absence of the metal ion) leads to dissociation of the tetramer.…”
mentioning
confidence: 99%
“…A conformational change has been identified in the metaldepleted form (apo-GDH) which, at low temperature and high pH, results in the inability of the enzyme to rebind metal ions. This form of the enzyme has an increased tendency towards dissociation of the oligomer particularly in tris and triethanolamine based buffers [3].…”
mentioning
confidence: 99%